Constructing a thesaurus to Mahāvamsa – a facet analytical approach - Arulanantham, S.; Navaneethakrishnan, S. (approachProceedings of 8th Annual Research Conference on the Humanities and Social Sciences the Royal Asiatic Society of Sri Lanka, 2015)
One of the effective mechanisms in the process of interactive retrieval is vocabulary control. The controlled vocabulary exists to facilitate communication in the information retrieval process. The complete set of index terms used in retrieval systems may be referred to as the vocabulary of index language of the systems. The establishment of thesaurus is one way of attaining a common indexing and searching tool suitable for the use of an ancient classical text. There are thesauri for popular sacred literature like Rigveda, Quran and Bible. Likewise indexing tool too should be constructed for each classical literature for the depth understanding and optimum level of usage for the readers. The main objective of this paper is to construct an English thesaurus to Mahāvamsa using facet analytical approach – as a suitable technique to act as a vocabulary guide to Mahavamsa.This paper attempts to design a thesaurus on Mahavamsa which could be act as working tool for the indexing and retrieval. Based on Descriptive method, meaning of each term and its semantic relationship with other terms were analyzed. Data analysis was based on Facet analytical approach devised by S.R.Ranganathan. This Thesaurus was constructed in English language using as input, facet analyzed subject headings derived from a collection of terms selected from standard English translation of Mahavamsa.This thesaurus adopts two methods of display. The main part of the thesaurus comprised of complete information of each descriptor arranged alphabetically. It includes Descriptors, scope notes, non preferred terms, Top Terms, broader, narrower and related terms. In the second part each descriptors are arranged according to subject classification order.
Keywords: Thesaurus; Information retrieval; Mahavamsa; Vocabulary control device